2019
DOI: 10.1177/0361198119846456
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Law Enforcement Response to Wrong-Way Driving Events in Florida

Abstract: Wrong-way driving (WWD) can result in severe crashes. By responding quickly to WWD dispatch calls, law enforcement officers (LEOs) could stop the wrong-way vehicle before a crash occurs. This paper analyzed law enforcement (LE) response times to WWD dispatch calls in Florida between January 2003 and April 2018 to determine significant effects. The average LE response time was much lower for 2013 onward than before 2013. Average response time was lower during nighttime and in urban areas and was higher for coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…If no mean was presented, we converted the unstandardized B coefficients into standardized Beta coefficients by extracting the standard deviation of both the outcome and the predictor variables. For the one study that presented results of an ordinal logit regression (Kayes et al, 2019), we converted the unstandardized B coefficients into odds ratios.…”
Section: Strength Of the Associationsmentioning
confidence: 99%
“…If no mean was presented, we converted the unstandardized B coefficients into standardized Beta coefficients by extracting the standard deviation of both the outcome and the predictor variables. For the one study that presented results of an ordinal logit regression (Kayes et al, 2019), we converted the unstandardized B coefficients into odds ratios.…”
Section: Strength Of the Associationsmentioning
confidence: 99%
“…Studies of Florida LED WWD countermeasures found that they have much lower turnaround percentages than RFBs, but can reduce WWD 911 calls and citations by up to 48% (5,6). Combined, Florida RFB and LED WWD countermeasures were estimated to have saved law enforcement officers over 116 h by confirming when detected wrong-way vehicles turn around (19). In Texas, analysis of LED WWD countermeasures installed on US 281 found a 30% reduction in WWD, resulting in an estimated B/C ratio of 13:1 for a 20-year life cycle (20).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers in Texas studied how intoxication affects a driver’s ability to identify signs and WWD countermeasures; they found that LEDs made it easier for intoxicated drivers to notice “Wrong Way” signs, but harder for them to read the signs ( 13 , 14 ). Studies of LED and RFB countermeasures in Florida by the authors showed that both devices reduce WWD, but RFBs are more effective and provide substantial life-cycle benefits ( 3 , 4 , 15 , 16 ). RFBs were also preferred over LEDs by surveyed drivers and law enforcement officers ( 17 ).…”
Section: Literature Reviewmentioning
confidence: 99%